Mineralogical Characterization of a Conventional Copper Refinery Anode Slimes Treatment Circuit - T. T. Chen (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
A detailed mineralogical study was carried out to characterize the products generated in a conventional copper refinery anode slimes treatment circuit. The anode slimes, which are first leached in sulphuric acid media under an oxygen pressure to dissolve the copper and much of the tellurium, were found to contain various Ag-Cu selenides, PbSO4, Ag, Au and BaSO4. The resulting Ag2Se, Ag3AuSe2, Se, Au, PbSO4, BaSO4, SnO2 and silicate-rich leach residue is dried and pelletized. It is subsequently roasted to convert the selenium to Ag2SeO3, volatile SeO2 and water soluble Na2SeO4. The roasted product, which was found to consist of Ag2Se, PbSe, PbSO4, BaSO4, Ag3AuSe2, Au and Sn02, is smelted and refined in a Dore furnace to produce a Dore metal that contains a (Ag,Au,Pd,Cu,Pt) alloy together with traces of CuO and a Cu-Pb oxide phase. Parting plant mud shown to contain AgC1, Ag, Au, (Au,Ag,Pd), Ag2Cu2O3 and Ag20, and scrubber mud containing PbSO4 and AgC1 are also fed to the Dore furnace. The Dore furnace sequentially separates a silica slag which was found to consist of Ag, Sn02, BaSO4, Pb-Sb oxide, Fe-Sb-Ni-Cr oxide and a Pb-rich silicate phase, a soda-rich slag containing Na2CO3.H2O and Na2(Se,Te)03, and a niter slag containing Na2TeO3, Na2(Se,Te)03 and a Na-Te-Se-Pb-Ba-Cu oxide phase. The Dore metal is electrorefined in Moebius cells to yield high-purity silver and a gold mud which was shown to consist of a (Au,Ag,Pd,Cu,Pt) alloy and traces of CuO. Silver is leached from the gold mud and the resulting gold sand is cast into anodes and electrorefined in Wohlwill cells to produce pure gold.